Validation of the Knowledge, Attitude, and Practice survey for self-care in leprosy - Charmenes Alves Gomes; Maria do Socorro Vieira Lopes; Sabrina Alaide Amorim Alves; Evanira Rodrigues Maia; Edilma Gomes Rocha Cavalcante; Cynthia Kelly Fernandes de Lima; José Wagner Martins da Silva (Universidade Federal do Ceará, 2024)
Objective: to validate the content of the Knowledge, Attitude, and Practice of self-care in the leprosy survey. Methods: a methodological study is developed in two stages: the development of the instrument and content validation by expert judges. The content of each item was validated for clarity. The Content Validity Index was used to assess agreement between the judges. Descriptive statistics were used to analyze the data. Results: five experts participated; the survey's content validity index was 0.87. 21 items were reformulated, 11 were included, and three were added to another domain. This resulted in 40 items distributed in three categories: face care (15 items), hands (12 items) and feet (13 items). Conclusion: the final version of the Knowledge, Attitude, and Practice survey covers the face, hands, and feet categories and has achieved adequate content validity for its use. Contributions to practice: this constitutes an essential tool that will help health professionals make decisions regarding practices to promote self-care for people with leprosy.